Community Tendencies in Decision Making towards the Selection of Health Service Places In Makassar City, Indonesia - Yasir Haskas (Jurnal Ilmiah Ilmu Administrasi Publik, 2022)
Hospitals are a very urgent need for people in unstable health conditions. Therefore, people choose hospitals that are able to provide the best service for people in need. The type of qualitative research through a phenomenological approach, while the results showed that the low use of health facilities was often due to the distance between hospitals and communities too far, high tariffs, unsatisfactory services, and that influenced the level of service utilisation, namely from health service providers, namely available facilities, service costs and distance, while the community itself as a user of health services, namely the social and socio-economic status of the community. This study aims to determine the tendency of the community in making decisions on the selection of health services in Makassar city. The population in this study were people who were queuing at several hospitals.